Keanekaragaman Lumut sebagai Bioindikator Kualitas Udara di Kawasan Taman Wisata Alam Suranadi dan Ruang Terbuka Hijau Udayana: Moss Plant Diversity as a Bioindicator of air Quality in Suranadi Natural Park and Green Open Space of Udayana - Isrowati Isrowati; Immy Suci Rohyani; Ernawati Ernawati; Cahyo Aditya Akbar; Elisa Darmayanti Wahyuni; Wildanniati Purnamasari (LPPM Universitas Mataram, 2023)
Different intensity of transportation in Suranadi Natural Park and Green Open Space of Udayana effected in air quality. Decreasing of the air quality will have a serious impact on the enviroment, human health and the economy. Moss can accumulate pollutants and is sensitive to air quality degradation. it can be used as a bioindicator. The aim of the research was to determine the diversity index, abundance index of mosses and analyze air quality in the TWA Suranadi and RTH of Udayana. The research method uses quadrant 10 x 10 m whic is placed by purposive sampling. The diversity index (H′) in TWA Suranadi is low category (H′=1.4) with 5 species founded. Species with a high abundance index were Andreae sp. (45.45%), Brachythecium rutabulum (18.18%) and Taxiphyllum sp. (18.18%), while Lejeunea laetevirens (9.09%) and Hypnum cupressiforme (9.09%) are low category. The index diversity in Udayana RTH is low category (H′=1.2) with 4 species founded. Species with a high abundance index were Octoblepharum albidum (44.44%), Dicranoweisia crispula (22.22%) and Lopholejeunea sp (22.22%), while Barbula sp (11.11%) was moderate category. The moss diversity index in TWA Suranadi is higher than in Udayana RTH. Air quality in both areas is still below the threshold. Air quality affects the diversity index. Periodic monitoring of air quality needs to determine the effectiveness of mosses in absorbing pollutants.